2016
DOI: 10.1080/13854046.2016.1202239
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X-associated tremor/ataxia syndrome: phenotypic comparisons with other movement disorders

Abstract: Distinct profiles in the cognitive and motor domains between these movement disorders may guide practitioners in the differential diagnosis process and ultimately lead to better medical management of FXTAS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 422 publications
(534 reference statements)
2
24
0
Order By: Relevance
“…Tremor is the most frequent symptom and is seen in 80 % of patients, cerebellar ataxia in 50 % and parkinsonism in 30 % (13). Most patients have mixed tremor, with tremors both at rest and during movement.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 4 more Smart Citations
“…Tremor is the most frequent symptom and is seen in 80 % of patients, cerebellar ataxia in 50 % and parkinsonism in 30 % (13). Most patients have mixed tremor, with tremors both at rest and during movement.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Dementia is also seen at advanced stages of the disease, and it is reported that as many as 50 % of male patients over the age of 55 fulfil criteria for dementia (13). Patients with fragile X-associated tremor/ataxia syndrome also have increased rates of anxiety and depression, with a lifetime prevalence of severe depression of 44 %, and of anxiety disorders of 52 % (14).…”
Section: Clinical Featuresmentioning
confidence: 99%
See 3 more Smart Citations